Creative Lawyering: Leveraging the Flexibility of Institutional Relationships to advance Social Justice--Two Case Studies from South Africa. (25th June 2021) - Chamberlain, Lisa
Abstract: While private sector legal work is characterised by attorney-client relationships of a relatively homogenous kind, social justice lawyering offers a myriad of different ways in which organisations can partner with each other. The social justice sector is infused with a diversity of different kinds of partners, but also great variety in the forms that those partnerships can take. This practice note discusses attempts to do this creatively in South Africa using the Mapungubwe Campaign and the mobilization of mining-affected communities around the Mining Charter as case studies, in order to draw out some principles to guide the establishment and maintenance of institutional partnerships. These principles include the need for a shared objective, the notion of 'gaps not glory', the importance of role clarity, having pre-existing relationships to draw on in times which call for urgent collaboration, and the need for dedicated training on the management of partner relationships within NGOs. Ultimately, if managed strategically, these kinds of institutional partnerships present an opportunity for human rights lawyers to leverage the flexibility of these institutional relationships in order to advance social justice.